Improving Bus Service Levels and social equity through bus frequency modelling. (January 2017) - Ruiz, Maurici; Segui-Pons, Joana Maria; Mateu-LLadó, Jaume
Abstract: Bus lines play an essential role in providing urban public transport service. Demographic and socioeconomic characteristics determine the specific transport service needs of districts that, in most cases, are not served by the existing bus routes. Small changes in the frequency of a bus route can have a direct effect on the territorial distribution of a city's public transport service. Adjusting the frequencies of a bus fleet can help planners improve the service level and adapt the fleet's spatial distribution. A bus frequency optimization methodology is proposed to improve harmonization between service level and social equity in public transport. The method relies on a simple spreadsheet that integrates geographic data about bus routes and socioeconomic information about city districts. Simulation and optimization procedures are coordinated to appropriately adjust the routes to the geographic space. The proposed method is tested in a real case study that demonstrates its usefulness in analysing the service level and equity of a transport system and improving a city's public transport planning. Highlights: An integrated methodology to improve the Bus Service Levels and the social equity is proposed. GIS linked to simulation and optimization tools give support to the management of public transport service. Small changes in the headways of bus lines can significantly enhance public transport service level and social equity.